Dihydroartemisinin enhances Apo2L/TRAIL-mediated apoptosis in pancreatic cancer cells via ROS-mediated up-regulation of death receptor 5. - Rui Kong; Guang Jia; Zhuo-xin Cheng; Yong-wei Wang; Ming Mu; Shuang-jia Wang; Shang-ha Pan; Yue Gao; Hong-chi Jiang; De-li Dong; Bei Sun (PLoS ONE, 2012)
BACKGROUND: Dihydroartemisinin (DHA), a semi-synthetic derivative of artemisinin, has recently shown antitumor activity in various cancer cells. Apo2 ligand or tumor necrosis factor-related apoptosis-inducing ligand (Apo2L/TRAIL) is regarded as a promising anticancer agent, but chemoresistance affects its efficacy as a treatment strategy. Apoptosis induced by the combination of DHA and Apo2L/TRAIL has not been well documented, and the mechanisms involved remain unclear. METHODOLOGY/PRINCIPAL FINDINGS: Here, we report that DHA enhances the efficacy of Apo2L/TRAIL for the treatment of pancreatic cancer. We found that combined therapy using DHA and Apo2L/TRAIL significantly enhanced apoptosis in BxPC-3 and PANC-1 cells compared with single-agent treatment in vitro. The effect of DHA was mediated through the generation of reactive oxygen species, the induction of death receptor 5 (DR5) and the modulation of apoptosis-related proteins. However, N-acetyl cysteine significantly reduced the enhanced apoptosis observed with the combination of DHA and Apo2L/TRAIL. In addition, knockdown of DR5 by small interfering RNA also significantly reduced the amount of apoptosis induced by DHA and Apo2L/TRAIL. CONCLUSIONS/SIGNIFICANCE: These results suggest that DHA enhances Apo2L/TRAIL-mediated apoptosis in human pancreatic cancer cells through reactive oxygen species-mediated up-regulation of DR5.